PROMOTIONAL STRATEGY TRAINING IN RESULTS MARKETING PRODUCTION AT MITRA MAJU FURNITURE TRADING BUSINESS IN BANDAR LABUHAN DISTRICT. TANJUNG MORAWA, DELI SERDANG REGENCY - Dewi Sundari; Rangga Salam; Ilfi Rahmi Putri; Liza Widya Hasyim; Anggi Pratiwi Sitoirus; Rodi Syafrizal (RADJA PUBLIKA, 2024)
The purpose of this service is to get an overview of the purpose of the Aek Parombunan community's participation as workers processing anchovies and cassava into chili chips in the Sambal Chips business Jl. Sisingamanangaraja in Aek Prombunan Village, Sibolga City is to help increase the income of the people of Aek Parambunan Sibolga Village. The method of implementing this community service is carried out regularly and is divided into several activities starting from the survey stage in the form of socialization which is carried out by compiling programs that will be delivered when community service activities take place, including preparing materials and schedules and dividing the tasks of the community service team. The initial stage is in the form of friendly relations with business owners and their employees, namely the Aek Parombunan community consisting of high school graduates and also those who are still in school who live in the Aek Parombuna sub-district. The results of the community service activities were obtained in the form of in-depth study of several industrial centers in the Aek Parombunan Village, Sibolga City, by processing anchovies and cassava into chili chips, which are typical souvenirs from the city of Sibolga. Empowerment of the Aek Prombunan sub-district community includes social, educational and economic dimensions, community empowerment strategies should consider characteristics such as age, skill, gender and ability to work in centers that are in this trading business location, and to realize Aek Parombunan sub -district community empowerment integration support from both local agencies and civil society, private and educational institutions is needed.